Aluminum alloy surface chromium-free conversion film and preparation method thereof
By forming a chemical conversion film composed of K2TiF6, K2ZrF6, KMnO4 and MgSO4 on the surface of the aluminum alloy, the pollution and corrosion resistance of the traditional chromate conversion coating are solved, and the efficient protection effect of chromium-free and environmentally friendly is achieved.
Patent Information
- Application Number
- CN202410706205.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119307901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical conversion films, and in particular to a chromium-free conversion film on the surface of an aluminum alloy and a preparation method thereof. Background Art
[0002] Traditional chromate conversion coatings are widely used on various aluminum alloys, magnesium alloys and other metals because of their significant adhesion promotion, good barrier properties and self-healing ability. However, with the increasing global industrial environmental awareness, the pollution problems caused by traditional chromate processes cannot be ignored.
[0003] In recent years, most research teams have been committed to developing chromium-free systems. The results include inorganic conversion coatings, such as Cr (III) conversion coatings; titanate and zirconate-based conversion coatings; molybdenum-based conversion coatings; organic conversion films and composite conversion films. Chinese patent application number CN201811419120.X discloses a method for preparing a titanium-zirconium-cerium chemical conversion film on an aluminum alloy surface, comprising: placing the aluminum alloy to be treated in a conversion solution for conversion treatment, wherein the conversion solution contains sodium hexametaphosphate and cerium nitrate hexahydrate. Although a chromium-free chemical conversion film is also prepared, its corrosion resistance and electrochemical corrosion resistance are relatively weak. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a chromium-free conversion film on the surface of an aluminum alloy and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a chromium-free conversion film on an aluminum alloy surface comprises the following steps: S1. Grind the aluminum alloy surface until smooth and then degrease it; S2. Alkaline etching is performed on the surface of the aluminum alloy after degreasing treatment; S3, after taking out, the aluminum alloy surface is successively subjected to immersion water washing and deionized water rapid rinsing, and then pickling; S4, after taking out, sequentially undergo immersion water washing and deionized water rapid rinsing, and then put the aluminum alloy into a chemical conversion solution with a pH of 2.6-4.5, and react at 15-55°C for 2-10 minutes; the chemical conversion solution is composed of the following components: K2TiF6 6g / l, K2ZrF6 6g / l, KMnO4 2-8g / l, and accelerator 0-6g / l; S5. After the reaction is completed, the surface of the aluminum alloy is washed with water and then dried to form a chemical conversion film on the surface of the aluminum alloy.
[0006] Preferably, the alkaline etching in step S2 is specifically as follows: the aluminum alloy after degreasing treatment is immersed in a mixed solution composed of 25g / l NaOH and 30g / l Na2CO3 at 45°C for 3 minutes.
[0007] Preferably, the pickling in step S3 is specifically as follows: the aluminum alloy is immersed in 200 g / l HNO3 at room temperature for 3 minutes.
[0008] Preferably, in steps S3 and S4, the immersion is performed for 2 minutes, and the deionized water is quickly rinsed for 3 minutes.
[0009] Preferably, the promoter is MgSO4.
[0010] Preferably, in step S4, the chemical conversion solution consists of the following components: K2TiF6 6g / l, K2ZrF6 6g / l, KMnO4 4g / l, acrylic acid 10ml / l, MgSO4 2g / l, pH 3.7, reaction temperature 6min, reaction time 35°C.
[0011] Preferably, in step S5, the surface of the aluminum alloy is washed with water and then dried at 60°C.
[0012] The chromium-free conversion film is prepared by the method for preparing the chromium-free conversion film on the surface of the aluminum alloy.
[0013] The beneficial effects of the present invention are: The present invention adopts a chromium-free and environmentally friendly formula to prepare a uniform and continuous golden titanium zirconium salt chromium-free conversion film, which has obvious color development on the substrate. It has good corrosion resistance as proved by various performance experiments and can provide good protection for aluminum alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The effect of different concentrations of K2TiF6 on the corrosion resistance of chromium-free conversion film; Figure 2 The surface diagram of aluminum alloy immersed in different concentrations of K2TiF6; Figure 3 The effect of different concentrations of K2ZrF6 on the corrosion resistance of chromium-free conversion film; Figure 4 The surface diagram of aluminum alloy immersed in different concentrations of K2TiF6; Figure 5 The effect of different concentrations of KMnO4 on the corrosion resistance of chromium-free conversion film; Figure 6 The surface diagram of aluminum alloy immersed in different KMnO4 concentrations; Figure 7 The effect of different concentrations of acrylic acid on the corrosion resistance of chromium-free conversion coating; Figure 8 The surface images of aluminum alloys immersed in different acrylic acid concentrations; Fig. 9 This is the surface diagram of aluminum alloy immersed in different additives; Fig.10 The effect of different MgSO4 concentrations on the corrosion resistance of chromium-free conversion film; Fig.11 The surface diagram of aluminum alloy immersed in different MgSO4 concentrations; Fig.12 are the polarization curves of different film-forming promoters; Fig.13 The Tafel curves of conversion films with different concentrations of magnesium sulfate in 3.5% NaCl solution; Fig.14 The corrosion resistant titration time of the conversion film formed at different temperatures and the appearance of the aluminum alloy substrate; Fig.15 The corrosion resistance titration time of the conversion film and the appearance of the aluminum alloy substrate at different pH values; Fig.16 The corrosion resistant titration time of the conversion film and the appearance of the aluminum alloy substrate at different times; Fig.17 is the orthogonal experimental result; Fig.18 is the Tafel curve of aluminum alloy before and after transformation; Fig.19 Impedance diagram of aluminum alloy before and after transformation; Fig. 20 This is the corrosion test result of 3.5%NaCl solution; Fig.21 This is a comparison of the bare aluminum surface and the prepared film layer under SEM electron microscope at a magnification of 5.00 μm; Fig. 22 This is a comparison of the bare aluminum surface and the prepared film layer under a SEM electron microscope with a magnification of 10.0 μm; Fig.23 This is a comparison of the bare aluminum surface and the prepared film layer under a SEM electron microscope with a magnification of 50.0 μm; Fig.24 This is the SEM electron microscope image of the holes on the bare aluminum surface at 3μm; Fig.25 This is the material analysis diagram of 7075 bare aluminum holes; Fig.26 This is an analysis diagram of the pore materials on the film-forming surface. DETAILED DESCRIPTION
[0015] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0016] The materials and instruments used in the following examples are: 7075 aluminum alloy (61mm×61mm×1.5mm); all chemicals used are analytically pure reagents; instruments used include: pH tester, SEM electron microscope workstation, electronic balance, electrochemical workstation, constant temperature water bath, digital display blower drying oven.
[0017] This experiment was carried out at room temperature, and single-factor tests were performed on each component in the process formula, and the best process formula was screened through drip experiments.
[0018] Potassium fluorotitanate (K2TiF6) and potassium fluorozirconate (K2ZrF6) were selected as the main film-forming salts to prepare chromium-free chemical conversion films on aluminum alloys. The effects of the concentration of the main titanium-zirconium salts, the concentration of the oxidant potassium permanganate, the concentration of the complexing agent acrylic acid, the film-forming promoter, the reaction temperature, the reaction time and the reaction pH on the corrosion resistance of the film were investigated.
[0019] 1. Influence of titanium salt concentration At 30-35℃, the treated 7075 bare aluminum substrate was immersed in 2g / l, 4g / l, 6g / l, and 8g / l K2TiF6 solutions for 6 minutes. After the film was formed and dried, the prepared potassium dichromate solution was used to titrate and observe the results to select the most suitable concentration. The corrosion resistance drip time and film appearance are shown in Table 3.1:
[0020] From Table 3.1, we can see that when the concentration of K2TiF6 is 6g / l, the corrosion resistance time is the longest, indicating the best effect. Figure 1 It was observed that the highest point was reached at 6 g / l, and it showed a downward trend after the concentration was increased. Figure 2 It was observed that the surface of the aluminum alloy with a K2TiF6 concentration of 6 g / l was relatively uniform, indicating that the corrosion resistance dripping time was the best when the K2TiF6 concentration was 6 g / l.
[0021] 2. Effect of zirconium salt concentration The selected 6 g / l K2ZrF6 was used as the basic solution, and different concentrations of K2ZrF6 were added on this basis: 2 g / l, 4 g / l, 6 g / l, 8 g / l, 10 g / l, and the treated 7075 bare aluminum was placed in the above mixed solution at a temperature of 30-35°C and soaked for 6 minutes. After the film was formed and dried, the prepared potassium dichromate solution was used to titrate and observe the results to select the most suitable concentration. The corrosion resistance drip time and film appearance are shown in Table 3.2:
[0022] From Table 3.2, we can see that when the concentration of K2ZrF6 is 6 g / l, the corrosion resistance titration time is the longest. Figure 3 It can be seen that the 6g / l K2ZrF6 curve reaches the highest point, and the curve shows a downward trend when the concentration increases. Figure 4 It can be seen that the film formed on the aluminum alloy surface is more uniform when the K2ZrF6 concentration is 6 g / l, which indicates that 6 g / l K2ZrF6 concentration is the best.
[0023] 3. Effect of film-forming oxidant KMnO4 concentration Join Mn 2+ In the Ti / Zr conversion film solution, the morphology of the conversion film is changed, the corrosion resistance is improved, and the processing time is shortened. 2+ The main components and structure of the conversion film are not changed. The selected 6 g / l K2TiF6 and 6 g / l K2ZrF6 are used as the basic solution, and different concentrations of KMnO4 are added on this basis: 2 g / l, 4 g / l, 5 g / l, 6 g / l, 8 g / l. The treated 7075 bare aluminum is immersed in the above mixed solution at a temperature of 30-35°C for 6 minutes. After the film is formed and dried, the prepared potassium dichromate solution is used to titrate and observe the results to select the most suitable concentration. The corrosion resistance titration time and film appearance are shown in Table 3.3:
[0024] From Table 3.3, we can see that when KMnO4 is 4 g / l, the corrosion resistance titration time is the longest. Figure 5 It can be seen that the curve reaches the highest point when the concentration is 4g / lKMnO4, and the curve shows a downward trend when the concentration increases. Figure 6 It can be seen that when the KMnO4 concentration is 4 g / l, the film formed on the aluminum alloy surface is more uniform and the color is obviously golden yellow. It can be inferred that 4 g / l KMnO4 concentration is the best.
[0025] 4. Effect of the concentration of acrylic acid as a film-forming complexing agent The selected 6 g / l K2TiF6, 6 g / l K2ZrF6, and 4 g / l KMnO4 were used as the basic solution. On this basis, different concentrations of acrylic acid were added: 5 ml / l, 10 ml / l, 15 ml / l, and 20 ml / l. The treated 7075 bare aluminum was placed in the above mixed solution at a temperature of 30-35°C and soaked for 6 minutes. After the film was formed and dried, the prepared potassium dichromate solution was used to titrate and observe the results to screen out the most suitable concentration. The corrosion resistance titration time and film appearance are shown in Table 3.4:
[0026] From Table 3.4, we can see that when the acrylic acid concentration is 10 ml / l, the corrosion resistance titration time is the longest. Figure 7 It can be seen that the curve reaches the highest point when the concentration of acrylic acid is 10 ml / l, and the curve shows a downward trend when the concentration increases. Figure 8 It can be seen that when the concentration of acrylic acid is 10 ml / l, the film formed on the aluminum alloy surface is more uniform and the color is obviously golden yellow. It can be inferred that the best concentration of acrylic acid is 10 ml / l.
[0027] 5. Screening of film-forming promoters.
[0028] The selected 6 g / l K2TiF6, 6 g / l K2ZrF6, 4 g / l KMnO4, and 10 ml / l acrylic acid were used as the basic solution. On this basis, 2 g / l of anhydrous sodium molybdate, tannic acid, CuSO4, anhydrous CaCl2, MgSO4, and NaH2PO4 were added respectively. The treated 7075 bare aluminum was placed in the above mixed solution at a temperature of 30-35°C and soaked for 6 minutes. After the film was formed and dried, it was titrated with the prepared potassium dichromate solution to observe the results. The corrosion resistance titration time and film appearance obtained are shown in Table 3.5:
[0029] Table 3.5 shows that the titration effects of anhydrous sodium molybdate, CuSO4, and anhydrous CaCl2 with potassium dichromate are not good. It may be that they react with the substances in the film-forming base solution, resulting in uneven film formation, colorless film formation, and other problems, resulting in reduced corrosion resistance of the film; the titration effect of tannic acid is OK, but not as good as MgSO4 and NaH2PO4. The titration time of MgSO4 and NaH2PO4 is basically the same. This shows that these two components are relatively good. However, according to Fig. 9 It can be clearly seen that MgSO4 has a distinct golden yellow and uniform film-forming color, while NaH2PO4 has a colorless film-forming color. In order to more conveniently observe the state of film formation, MgSO4 was finally selected as the film-forming promoter.
[0030] There are two key references for evaluating the corrosion resistance of metal materials: 1. Based on the thermodynamic theory, the smaller the value of the self-corrosion potential (Ecorr), the greater the development trend of corrosion changes; the larger the value of Ecorr, the smaller the development trend of corrosion changes. However, this judgment only considers thermodynamics and ignores the kinetic characteristics. Therefore, this indicator can only be used to evaluate the corrosion difficulty of materials, not to evaluate their corrosion resistance. 2. Based on the kinetic characteristics of the material, the smaller the value of the self-corrosion current density (icorr), the smaller the corrosion rate. The larger the effective value of icorr, the greater the corrosion rate.
[0031] Fig.12 The different Tafel curves of the conversion films generated by the accelerators are shown, and Table 3.7 lists the electrochemical parameters fitted based on the polarization data. Fig.12 From Table 3.7, we can know that the lowest self-corrosion potential of the conversion film on the aluminum alloy surface is the fluorescent green curve, anhydrous CaCl2 is -1.0148 V, and the highest is the brown curve, MgSO4 is -0.7607 V. The self-corrosion current density of anhydrous CaCl2 is 5.223×10 -5 A.cm -2 , the effective density of self-corrosion current of MgSO4 is 3.651×10 -6 A.cm -2 In contrast, the self-corrosion current density of MgSO4 is less than that of anhydrous CaCl2. And the corrosion current density of other reagents is greater than that of MgSO4. It can be concluded that MgSO4 is the most suitable film-forming promoter.
[0032]
[0033] 6. Effect of magnesium sulfate concentration The concentration of MgSO4 was screened on the basis of the determined basic solution concentrations of K2TiF6 at 6 g / l, K2ZrF6 at 6 g / l, KMnO4 at 4 g / l, and acrylic acid at 10 ml / l. At a temperature of 30-35°C, the treated aluminum alloy was immersed in a mixed solution of 1 g / l, 2 g / l, 4 g / l, 6 g / l MgSO4 solution and the basic solution for 6 minutes. After film formation and drying, the prepared potassium dichromate solution was used to titrate and observe the results to screen out the most suitable concentration. The corrosion resistance titration time and film appearance obtained are shown in Table 3.6:
[0034] From Table 3.6, we can see that when the concentration of K2TiF6 is 6 g / l, the concentration of K2ZrF6 is 6 g / l, the concentration of KMnO4 is 4 g / l, the concentration of acrylic acid is 10 ml / l, and the concentration of MgSO4 is 2 g / l, the corrosion resistance titration time is the longest. Fig.10 It can be seen that the 2 g / l MgSO4 curve reaches the highest point, and the curve shows a downward trend when the concentration increases. Fig.11 It can be seen that when the MgSO4 concentration is 2 g / l, the film formed on the aluminum alloy surface is more uniform and the color is obviously golden yellow. It can be inferred that 2 g / l MgSO4 concentration is the best.
[0035] Depend on Fig.13 From Table 3.8, it can be concluded that the highest self-corrosion potential of the conversion film on the aluminum alloy surface is -0.7607 V at 2 g / l MgSO4. The self-corrosion current density of 2 g / l MgSO4 is 3.651×10 -6 A.cm -2 In contrast, the corrosion current density of other concentrations of MgSO4 is greater than that of 2 g / l MgSO4. It can be concluded that 2 g / l MgSO4 is the most suitable concentration, which is consistent with the previous drip experiment.
[0036]
[0037] After determining the above-mentioned K2TiF6 concentration, K2ZrF6 concentration, oxidant KMnO4 concentration, complexing agent acrylic acid concentration, and promoter MgSO4 concentration, the process parameters can be optimized.
[0038] Through single factor experiments, 7075 bare aluminum alloy was directly immersed in the best film-forming formula that had been screened out: 6 g / l K2TiF6, 6 g / l K2ZrF6, 4 g / l KMnO4, 10 ml / l acrylic acid, 2 g / l MgSO4. Five-level single factor optimization experiments were conducted on the film-forming conditions (temperature, pH, time) to improve the optimization of conditions and enhance the corrosion resistance of the film layer.
[0039] 1. Determination of reaction temperature The chemical conversion liquid reaction temperature was set at 15-55℃, and a five-level single factor experiment was conducted. The experimental results show that Fig.14 ,Depend on Fig.14 It is known from the experiment that when the reaction temperature is 35℃, the corrosion resistance of the conversion film reaches the best, and the appearance of the film is more uniform. Lower temperature is not conducive to the reaction; while when the temperature is too high, the ions are more active, so it is not easy to form a film. In summary, the best reaction temperature of the conversion solution is 35℃.
[0040] 2. Determination of reaction pH When the temperature was 35℃, the pH of the chemical conversion solution was adjusted between 2.6 and 4.5, and a five-level single factor experiment was conducted. The experimental results show that Fig.15 .Depend on Fig.15 It can be seen that pH has a great influence on the film-forming solution. The poor titration effect of the film layer at low and high pH may be due to the unstable complexation of the conversion solution. When pH=3.7, the corrosion resistance of the conversion film is the longest, and the appearance of the film is uniform yellow. Therefore, the optimal pH of the conversion solution is determined to be 3.7.
[0041] 3. Determination of reaction time A five-level single factor experiment was conducted at a temperature of 35°C and pH = 3.7. The aluminum alloy was immersed in the conversion solution for 2-10 minutes to wait for film formation. The experimental results are shown in Fig.16 .Depend on Fig.16 It can be concluded that under the condition of 6 minutes of immersion, the chromate drip resistance time is the longest and the film layer is golden yellow. Therefore, it is judged that its corrosion resistance effect is the best. Too short a time may lead to incomplete film formation.
[0042] 4. Orthogonal experiment.
[0043] The four factors of potassium permanganate concentration, acrylic acid concentration, time and solution pH were selected to explore their effects on the corrosion resistance of the conversion film. An orthogonal experiment with four factors and three levels was designed, as shown in Table 4.4, to optimize the process parameters of the aluminum alloy conversion film:
[0044] Fig.17 This is the result of orthogonal experiment. According to the analysis of chromate resistance dripping time and film appearance, the optimal film formation process is pH=3.7, reaction time 6 min, potassium permanganate 4 g / l, acrylic acid 10 ml / l, and the optimal dripping time is 49 seconds. Fig.17 It is the result of orthogonal experiment to determine the optimal combination, with the drip time as the criterion.
[0045] Table 4.6 is the result of orthogonal experiment range analysis. In Table 4.6, Yi represents the total drip time at level i, Xi represents the arithmetic mean at level i, and R represents the range:
[0046] From Table 4.6, we can see that the order of the factors affecting the corrosion resistance of the film layer is pH>KMnO4 concentration>acrylic acid concentration>time. The pH range is the largest, which is the core and main influencing factor. The potassium permanganate concentration ranks second. The similar range indicates similar influence. The acrylic acid concentration and time factors have the smallest influence. So far, the analysis shows that the optimized film-forming formula process is: 6g / l K2TiF6, 6 g / l K2ZrF6, 4 g / l KMnO4, 10 ml / l acrylic acid, 2 g / l MgSO4, film-forming time 6 minutes, pH=3.7, and temperature 35℃.
[0047] Application examples: S1. Grind the aluminum alloy surface until smooth and then degrease it; S2, immersing the degreased aluminum alloy in a mixed solution of 25 g / l NaOH and 30 g / l Na2CO3 at 45°C for 3 min; S3, after taking out, immerse in water for 2 minutes, quickly rinse with deionized water for 3 minutes, and then immerse the aluminum alloy in 200g / l HNO3 at room temperature for 3 minutes; S4, after taking out, immerse in water for 2 minutes, quickly rinse with deionized water for 3 minutes, and then put the aluminum alloy into a chemical conversion solution with a pH of 3.7, and react at 35°C for 6 minutes; the chemical conversion solution consists of the following components: K2TiF6 6g / l, K2ZrF6 6g / l, KMnO4 4g / l, acrylic acid 10ml / l, MgSO4 2g / l; S5. After the reaction is completed, the surface of the aluminum alloy is washed with water and then dried at 60° C., thereby forming a chromium-free conversion film on the surface of the aluminum alloy.
[0048] In order to verify the performance of the chromium-free conversion film in the application example, the following tests were carried out: 1. Electrochemical performance test under optimal conditions Through the analysis of the above experimental results, the best process for preparing the conversion film has been obtained. Under the optimal conditions, the corrosion-resistant conversion film of 7075 bare aluminum alloy and the blank 7075 bare aluminum alloy were tested for Tafel test, and the Tafel curve was obtained as follows: Fig.18 The impedance diagram obtained is shown as Fig.19 By arranging the Tafel and impedance data, the self-corrosion potential and self-corrosion current density are shown in Table 4.7.
[0049] Through electrochemical testing, it was found that the self-corrosion current density in the Tafel curve of the aluminum alloy specimen immersed in the optimal film-forming solution was two orders of magnitude lower than that of the blank specimen. The impedance became larger with the optimization of the film, and the impedance of the film-forming aluminum alloy increased by 11270 ohm compared with the blank, which conforms to the rule that the larger the impedance, the better the corrosion resistance. It can be seen that the corrosion resistance of the 7075 bare aluminum alloy increased after being treated with the conversion solution.
[0050]
[0051] 1. Salt water immersion experiment The aluminum alloy specimens were directly immersed in 3.5% NaCl solution, and the changes in the film layer and the actual corrosion condition were observed after 168 h. Fig. 20 This is the corrosion test result of chemical conversion film in 3.5% NaCl solution.
[0052] After 20 minutes of corrosion test on the blank specimen, bubbles began to appear on the substrate surface; after 40 minutes of corrosion test on the titanium zirconium salt, bubbles began to appear on the substrate surface; after 60 minutes of corrosion test on the titanium zirconium salt + KMnO4 solution, bubbles began to appear on the substrate surface; the time for bubbles to appear on the substrate in the titanium zirconium salt + KMnO4 + acrylic acid solution was 120 minutes; the time for bubbles to appear on the substrate in the titanium zirconium salt + KMnO4 + acrylic acid + MgSO4 solution was 150 minutes. After 168 hours, it was observed that the blank specimen surface had the most serious pitting corrosion and the substrate turned black seriously; the pitting corrosion area on the substrate surface in the optimal solution was the smallest, about 1 / 12 of the blank area. The color of the film layer did not change much. It can be seen that the corrosion resistance is the best.
[0053] 2. SEM electron microscope experiment The data obtained by SEM electron microscope observation (5.00 μm, 10.0 μm, 50.0 μm) of the bare aluminum surface and the prepared film layer are shown in Fig.21 , Fig. 22 and Fig.23 .
[0054] pass Figure 21-24 It can be seen that there are many holes of different shapes, uneven dispersion and inner diameters on the surface of blank bare aluminum. These holes have a certain depth, and copper enrichment appears in some holes. Copper is one of the main reasons for the poor corrosion resistance of aluminum alloy. Figure 21-24 It can be seen that the surface of the optimal conversion film is composed of many crystal-like and relatively uniform substances, and the surface of the conversion film is more uniform than the bare aluminum surface. The inside of the pores is also covered with a uniform film layer. It can be seen that the film is more uniform, thereby improving the corrosion resistance. Through electron microscopy observation, it was found that there were more pores on the bare aluminum surface, such as Fig.24, and there are some substances in the holes. The results of elemental analysis of the substances in the holes on the bare aluminum surface are as follows Fig.25 As shown in the figure, the element analysis results of the substances in the holes on the surface of the conversion film are as follows Fig.26 shown.
[0055] Through orthogonal experimental analysis, the process parameters of the best corrosion-resistant solution were determined: temperature of 35°C, immersion for 6 minutes, pH = 3.7. Through the study of the Tafel curve and impedance diagram of the conversion film prepared under the optimal process parameters in electrochemistry, it was found that the self-corrosion current density of the optimal conversion film was reduced by 2 orders of magnitude compared with the blank, and the impedance of the film-forming aluminum alloy was increased by 11270 ohm compared with the blank. The SEM electron microscope magnified the state of the film layer and found that the film layer was relatively evenly covered on the surface of the aluminum alloy and filled the holes on the bare aluminum surface. After immersion in 3.5% sodium chloride solution for 168 h, it was found that the optimized film had the least corrosion area, indicating that the conversion film generated under the optimal conditions can resist the corrosion of sodium chloride solution for a long time.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a chromium-free conversion film on an aluminum alloy surface, characterized in that: The following steps are involved: S1. Grind the aluminum alloy surface until smooth and then degrease it; S2. Alkaline etching is performed on the aluminum alloy surface after degreasing treatment; S3, after taking out, the aluminum alloy surface is successively subjected to immersion water washing and deionized water rapid rinsing, and then pickling; S4, after taking out, sequentially immerse and wash with water, quickly rinse with deionized water, and then put the aluminum alloy into a chemical conversion solution with a pH of 2.6-4.5, and react at 15-55°C for 2-10 minutes; the chemical conversion solution is composed of the following components: K2TiF66g / l, K2ZrF66g / l, KMnO42-8g / l, and accelerator 0-6g / l; S5. After the reaction is completed, the surface of the aluminum alloy is washed with water and then dried to form a chemical conversion film on the surface of the aluminum alloy.
2. The method for preparing a chromium-free conversion film on an aluminum alloy surface according to claim 1, characterized in that: The alkaline etching in step S2 is specifically as follows: the aluminum alloy after degreasing treatment is placed in a mixed solution composed of 25g / l NaOH and 30g / l Na2CO3 at 45°C and immersed for 3 minutes.
3. The method for preparing a chromium-free conversion film on an aluminum alloy surface according to claim 2, characterized in that: The pickling in step S3 is specifically as follows: the aluminum alloy is immersed in 200 g / l HNO3 at room temperature for 3 minutes.
4. The method for preparing a chromium-free conversion film on an aluminum alloy surface according to claim 1, characterized in that: In the steps S3 and S4, the mixture is immersed in water for 2 minutes and then quickly rinsed with deionized water for 3 minutes.
5. The method for preparing a chromium-free conversion film on an aluminum alloy surface according to claim 1, characterized in that: The promoter is MgSO4.
6. The method for preparing a chromium-free conversion film on an aluminum alloy surface according to claim 1, characterized in that: In step S4, the chemical conversion solution consists of the following components: K2TiF66g / l, K2ZrF66g / l, KMnO44g / l, acrylic acid 10ml / l, MgSO42g / l, pH 3.7, reaction temperature 6min, reaction time 35°C.
7. The method for preparing a chromium-free conversion film on an aluminum alloy surface according to claim 1, characterized in that: In step S5, the surface of the aluminum alloy is washed with water and then dried at 60°C.
8. A chromium-free conversion film prepared on the surface of an aluminum alloy by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of aluminum alloy surface titanium zirconium cerium chemical conversion coating
CN109207972A